E-Conosmart 2.0: Dissemination of General Education - Siti Nurjanah, Suparno, Margunani (International Journal of Advanced Science and Technology, 2020)
The problem of moral decadence that occurs among students, can be overcome through the application of general education or general education. This is in line with the mandate of Kemenristekdikti which requires that general education be present in the curriculum. In this regard, researchers conducted this research and development, by offering output in the form of E-conosmart 2.0, economic learning plus general education needed such as anti-corruption, defending the country, tolerance, diversity, multiculturalism, disaster mitigation, and tax awareness, which are packaged in Playstore, Appstore, Twitter, Facebook and Instagram in the form of intensive Qoutes that provide life lessons. Research and development of E-conosmart 2.0 aims to instill and strengthen the noble morals and character of the nation into young people, especially students. The development of E-Conosmart 2.0 has gone through various stages, and this is a continuation of the previous E-Conosmart program. The development is carried out following the stages of development according to Borg and Gall, namely the assessment of the situation, planning, manufacturing of initial products, initial trials, product improvements, and actual trials. In this regard, E-Conosmart 2.0 has gone through the stages of development to the manufacture of the initial product, and is expected to completen all stages of this year . Keywords: General Education, Industrial Revolution 4.0, E-conosmart 2.0.